STRATEGI MELAHIRKAN MAHASISWA PENGUSAHA PEMULA (STUDI KASUS MAHASISWA UNIVERSITAS MUHAMMADIYAH JAKARTA) - Jaharuddin Jaharuddin; Irfan Purnawan; Rully Mujiastuti; Rahmita Nurul Muthmainnah; Meri Prasetyawati (Universitas Sebelas Maret, 2019)
Young people begin his/her entrepreneurial through entrepreneurship programs initiated by various institutions so millennials are increasingly aware of entrepreneurship, some have even engaged in a startup business. The big challenge is how to keep the business spirit alive among millennials and how to equip these studentpreneur in solving various challenges in their business so they can survive and succeed. Entreprenurship development program (Program Pengembangan Kewirausahaan/PPK) at Business Incubator and Entrepreneurship Centre (Pusat Inkubator Bisnis dan Kewirausahaan /PIBK) at Universitas Muhammadiyah Jakarta (UMJ) could answer these challenges. PPK PIBK UMJ collected business proposals from students, selected the business proposals for further funding (these are called tenants), provided the tenants with courses (marketing strategy, finance report and mind set entrepreneurship), monitored omzette and evaluated the productivity of tenants every three months from februari 2017 until januari 2018. Source of PPK PIBK UMJ were funded by Ministry of Research Technology and Higher Education Republic of Indonesia. There were 85 business proposals from UMJ students. 20 proposals were selected as tenants in PPK PIBK UMJ. Of the 20 tenants at the end of 2018, 5 tenants achieved omzette over 5 million IDRs per months with continuous productivity. These 5 tenants were considered as independent startups. In conclusion, PPK PIBK UMJ in 2018 yield 5 independent startups.Keywords: Entrepreneurship, startup business, student preneur, business incubator, tenants, independent startups